Level of involvement in village administration and development activity among village development and security committee in village vision movement: an analysis of Malaysian case - Abu Samah, Bahaman; Mohamed Shaffril, Hayrol Azril; Alby, Jeffrey Lawrence D'Silva (EuroJournals Publishing, 2009)
The main objective of this study is to determine the level of involvement among Village Development and Security Committee (VDSC) in Village Vision Movement (VVM) in Malaysia. This study also intends to discover factors that influence it. A total of 235 respondents were involved in this study from three zones in Malaysia. Each zone was represented by a state whereby Selangor represented the central zone, Negeri Sembilan represented the southern zone and Pahang represented the east coast zone. Generally, it was identified that majority of VDSC members possessed moderate level of involvement. Results gained concluded that zone where respondents lived and education achievement have significant differences with the level of involvement while period of holding a position in VDSC and income were found to have significant and positive relationship with the level of involvement among VDSC members in village administration and development matters.